[Ti(fpin)3]2−: a structurally characterized transition metal tris(perfluoropinacolato) complex. Issue 18 (5th May 2021) - Heinemann, Jan; Klüfers, Peter
Abstract: The reaction of TiCl3  ⋅ 3THF with perfluoropinacol (H2 fpin), triethylamine and silver nitrite in acetonitrile yielded in the formation of the first tris(perfluoropinacolato) complex with a transition metal, (HNEt3 )3 [Ti IV (fpin)3 ]NO2 (1) . The compound was fully characterized with IR and UV‐vis spectroscopy as well as elemental analysis and single crystal X‐ray diffraction. The structure of 1 is compared with that of known homoleptic titanium(IV) compounds and the only other structurally resolved tris(perfluoropinacolato)metallate, the stannate(IV) (HNEt3 )2 [Sn(fpin)3 ] ⋅ 2acetone. Abstract :